Coping strategies in young healthy individuals with type D personality - Aleksei N. Sumin; Ingrid Yu. Prokashko; Anna V. Shcheglova (Russian Open Medical Journal)
Objective — To study the choice of coping strategies and coping intensity in healthy individuals with type D personality. Material and methods — The study included 98 students of Kemerovo State Medical University (KemSMU), 68 women and 30 men (their mean age was 19.1±2.0 years). All subjects filled out psychological questionnaires to identify type D personality (DS-14) and the choice of coping strategies (Ways of Coping Questionnaire (WCQ) and Coping Strategy Indicator (CSI)). Results — The participants were divided into a group with type D personality (n=44) and without it (n=54). Individuals with type D personality had higher scores on the Escape-Avoidance (p<0.001), Accepting Responsibility (p=0.009) and Distancing (p=0.05) scales of the WSQ questionnaire, and Avoidance strategy scale of the CSI questionnaire (p=0.007). Students with type D personality were characterized by a pronounced preference for the Escape-Avoidance strategy (p=0.000018). An increase of 1 point in the values on the Escape-Avoidance scale improved the chance of identifying type D personality by 1.15 times (p<0.001). An increase in scores on the Positive Reappraisal scale reduced the likelihood of identifying type D personality (OR 0.98; p=0.005). The Escape-Avoidance coping strategy was rather strongly associated with type D personality (AUC=0.779). Conclusion — In healthy young people with type D personality, inadequate coping strategies were notably prevalent: the Escape-Avoidance strategy identified by WCQ, and the Avoidance strategy marked by the CSI. The Escape-Avoidance strategy was independently associated with type D personality, and the Positive Reappraisal strategy was associated with the non-D type.